A general, a colonial crisis, and a nationalist schism: Primo de Rivera and the gaullist paradigm - Pack, Sasha D. (Hispania Nova, 2021)
This article develops hitherto unexplored comparisons between the Rif War and the Algerian War of Independence. The Rif War and the colonial policy of the Primo de Rivera dictatorship have been placed in various useful comparative frames, but these have tended to isolate specific elements of the overall history, eschewing the interrelationships between processes of domestic politics, international politics, and colonial warfare. Looking beneath the major differences between the Spanish experience in the Rif and the French in Algeria, three illuminating parallels emerge: (1) the emergence of a military “strongman” with the initial support of the colonial army despite his uncertain commitment to the army’s goals; (2) an international dynamic that circumscribed any real capacity for each “strongman” to dictate colonial policy; and (3) schism on the nationalist right of each country as a result of the conflict, pitting those who favored operating within the hegemonic international framework against those who organized against that framework. Although imperfect in many respects, this comparison emphasizes interrelated processes of politics, colonialism, and national identity.
Keywords: Rif War; Miguel Primo de Rivera; War of Algerian Independence; colonialism; Charles de Gaulle; spanish foreign policy; french foreign policy